LIFE CYCLE ASSESSMENT OF GRANULATED COCONUT SUGAR PRODUCTION FARMERS LEVEL IN PURWOREJO - Rizki, Fajar; Ismayana, Andes; Yani, Moh (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
Granulated coconut sugar is a powdered coconut sugar manufactured by Purworejo farmers from the sap of the coconut. Farmers' usage of simple technologies is the primary cause of environmental problems due to poor efficiency levels and uncontrolled emission emissions. The objectives of this research were to identify the stages of the granulated coconut sugar production farmer level process, from coconut sap to farmers' granulated coconut sugar, and then analyze the total environmental impact of granulated coconut sugar production farmer level process using the Life Cycle Assessment (LCA) approach and the CML-IA Baseline calculation method. The study's scope included an inventory of